Search for the decays B0s→[tau]+[tau]− and B0→[tau]+[tau]− - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; De Cian, Michel; Comerma-Montells, Albert; Esen, Sevda; Färber, Christian; Gerick, David; Gersabeck, Evelina; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2017)
A search for the rare decays B0s→τ+τ− and B0→τ+τ− is performed using proton-proton collision data collected with the LHCb detector. The data sample corresponds to an integrated luminosity of 3 fb−1 collected in 2011 and 2012. The τ leptons are reconstructed through the decay τ−→π−π+π−ντ. Assuming no contribution from B0→τ+τ− decays, an upper limit is set on the branching fraction B(B0s→τ+τ−)<6.8×10−3 at the 95% confidence level. If instead no contribution from B0s→τ+τ− decays is assumed, the limit is B(B0→τ+τ−)<2.1×10−3 at the 95% confidence level. These results correspond to the first direct limit on B(B0s→τ+τ−) and the world’s best limit on B(B0→τ+τ−).